The role of a reverse vortex finder for the design of a high performance uniflow cyclone. Issue 3 (4th March 2023) - Zhang, Shuo; Shin, Weon Gyu
Abstract: Swirl vane uniflow cyclones have advantages of a compact structure and low pressure drop but the problem of low particle collection efficiency. In the present study, we demonstrated that the performance of a swirl vane uniflow cyclone can be significantly improved by installing a reverse vortex finder (RVF) behind the swirl vane additionally. It was found that the RVF can act as a vortex stabilizer, which can lower the turbulent kinetic energy and eliminate the central vortex swing phenomenon, resulting in a low pressure drop and increasing the particle collection efficiency. In addition, the RVF can not only increase the particle residence time but also form vortex flow inside the RVF resulting in the enhance particle collection efficiency. Finally, we demonstrated that our newly designed swirl vane uniflow cyclone with a RVF has the best performance among various types of cyclones. Copyright © 2023 American Association for Aerosol Research